2017
DOI: 10.2527/jas.2016.0873
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lignocellulose and low or high levels of sugar beet pulp on nutrient digestibility and the fecal microbiota in dogs

Abstract: Lignocellulose is an alternative fiber source for dogs; however, it has not yet been studied as a feed ingredient for the nutrition of dogs. Eight adult Beagles were involved in the study, which consisted of 3 feeding periods of 8 to 12 wk each. All dogs received 3 different diets, which either had the same concentration of fiber sources (2.7% sugar beet pulp or lignocellulose) or were formulated for a similar concentration of approximately 3% crude fiber: 12% sugar beet pulp (highSBP; 3.1% crude fiber), 2.7% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 32 publications
4
30
0
Order By: Relevance
“…Feeding fructooligosaccharide (FOS) has been shown to increase potentially beneficial Lactobacillus and Bifidobacterium populations and reduce potentially detrimental C. perfringens in one study in dogs (Swanson et al, 2002); a second study suggested FOS interacted with dietary protein resulting in lower measured fecal Bifidobacterium when fed with a low protein diet and higher measured fecal Bifidobacterium when fed with a high protein diet (Pinna et al, 2018). Other studies in dogs fed diets supplemented with beet fiber showed that those fed higher concentrations of beet pulp had significant changes in gut microbial composition, marked in one study by decreased Fusobacteria and increased Firmicutes (Middelbos et al, 2010) and in another by increased Lactobacillus spp., Bifidobacterium spp., Clostridium coccoides cluster and Clostridium leptum cluster (Kröger et al, 2017), though a third study did not show significant differences (Maria et al, 2017). Finally, a study evaluating a mix of carbohydrate sources (containing 0.07% concentrations of apple pectin, inulin, arabinoxylan-oligosaccharides, resistant starch type III, galactomannan and β-glucan) showed that complex non-digestible carbohydrate substrates and substrate mixtures may have a significant impact on gut microbiota composition and diversity (Chung et al, 2019).…”
Section: Complex Carbohydratesmentioning
confidence: 94%
“…Feeding fructooligosaccharide (FOS) has been shown to increase potentially beneficial Lactobacillus and Bifidobacterium populations and reduce potentially detrimental C. perfringens in one study in dogs (Swanson et al, 2002); a second study suggested FOS interacted with dietary protein resulting in lower measured fecal Bifidobacterium when fed with a low protein diet and higher measured fecal Bifidobacterium when fed with a high protein diet (Pinna et al, 2018). Other studies in dogs fed diets supplemented with beet fiber showed that those fed higher concentrations of beet pulp had significant changes in gut microbial composition, marked in one study by decreased Fusobacteria and increased Firmicutes (Middelbos et al, 2010) and in another by increased Lactobacillus spp., Bifidobacterium spp., Clostridium coccoides cluster and Clostridium leptum cluster (Kröger et al, 2017), though a third study did not show significant differences (Maria et al, 2017). Finally, a study evaluating a mix of carbohydrate sources (containing 0.07% concentrations of apple pectin, inulin, arabinoxylan-oligosaccharides, resistant starch type III, galactomannan and β-glucan) showed that complex non-digestible carbohydrate substrates and substrate mixtures may have a significant impact on gut microbiota composition and diversity (Chung et al, 2019).…”
Section: Complex Carbohydratesmentioning
confidence: 94%
“…Cecal digesta from 10 chickens per treatment group (n = 10) were collected, instantly frozen in liquid nitrogen, and stored at −80°C. The analysis of the total concentration of bacterial metabolites was performed as described earlier ( Kröger et al., 2017 ). The total concentration of short-chain fatty acids ( SCFAs ) was determined by gas chromatography (Agilent 6890N, Agilent Technologies, Böblingen, Germany, autosampler G2614A, and injection tower G2613A, Network GC Systems, Böblingen, Germany) equipped with a flame ionization detector.…”
Section: Methodsmentioning
confidence: 99%
“…Lignocellulose, a constituent of plant cell walls, is mainly composed of insoluble NSP cellulose and hemicellulose as well as phenolic lignin ( Liu et al., 2014 ). In the last decade, few studies examined the use of dietary lignocellulose for different farm and companion animals revealing potential effects on digestive physiology and function ( Abad et al., 2013 ; Kröger et al., 2017 ; Slama et al., 2020 ). With respect to poultry nutrition, the feeding of lignocellulose at inclusion levels below 1% could improve broiler performance ( Sarikhan et al., 2010 ; Makivic et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Short-chain fatty acids (SCFA) in crop and caecum contents were analyzed as described previously [48]. In short, SCFAs were analyzed using gas chromatography (Agilent Technologies 6890N, autosampler G2614A, and injection tower G2613A; Network GC Systems, Böblingen, Germany) equipped with a flame ionization detector.…”
Section: Analysis Of Bacterial Metabolitesmentioning
confidence: 99%